Hazard-based duration modelling of merging time interval on freeway on-ramps. Issue 1 (21st December 2022) - Li, Ye; Zhu, Jichen; Haque, Md Mazharul; Lee, Jaeyoung
Abstract: Freeway on-ramps suffer high crash risks due to frequent merging behaviours. This study developed hazard-based duration models to investigate the merging time interval on freeway on-ramps based on microscopic trajectory data. Fixed effect, random effect and random parameters Weibull distributed accelerated failure time models were developed to capture merging time as a function of various dynamic variables. The random parameters model was found to outperform the two counterparts since the unobserved heterogeneity of individual drivers was captured. Modelling estimation results indicate that drivers along the merging section with an auxiliary lane perform a smooth merging process and are easily affected by speed variables. Dynamics of leading and following vehicles on the merging and target lanes are found to influence the merging time interval for merging without an auxiliary lane, whereas the influence of surrounding vehicles is marginal for those with an auxiliary lane. The findings of this study identify potential countermeasures for improving safety during the merging process.